Newly developed compact magnetic sector mass spectrometer. (14th November 2017) - Meng, Dong; Yongjun, Cheng; Wenjun, Sun; Meiru, Guo; Lian, Chen; Huzhong, Zhang; Gang, Li; Xiaoqiang, Pei
Abstract: In this paper, a novel compact magnetic sector mass spectrometer has been developed and tested at the Lanzhou Institute of Physics. Its design is based on the mass separation of a 90° magnetic sector-field analyzer with a double trajectory, which has a magnetic induction of 0.7 T. The instrument can record mass range from 1 to 50 amu based on two special trajectories when the accelerating voltage of the ion source changes from 200 V to 2500 V. The dimensions of the device together with the electronic unit are approximately 220  ×  165  ×  165 mm 3 (length  ×  depth  ×  height). The weight is 10.2 kg and the maximum power consumption was measured to be 20 W. The instrument successfully provided mass spectrum information on the vacuum test chamber, resolving power of about 58 at full width half maximum (FWHM), and demonstrated a sensitivity of 7.2  ×  10 −5 A Pa −1 . The compact magnetic sector mass spectrometer is designed for space application and can be extended to other portable analytical fields on Earth.